1997
DOI: 10.1124/mol.51.6.1077
|View full text |Cite
|
Sign up to set email alerts
|

Carbamazepine Inhibition of Neuronal Na+ Currents: Quantitative Distinction from Phenytoin and Possible Therapeutic Implications

Abstract: Carbamazepine and phenytoin, two of the most commonly prescribed antiepileptic drugs, have been proposed to share a similar mechanism of action by use-dependent inhibition of Na+ channels. The proposed similar mechanism of action, however, cannot explain the common clinical experiences that the two drugs are different; in some patients, one drug may be more effective than the other. This may occur even when optimal therapeutic concentrations are reached with both medications in plasma or the cerebrospinal flui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
125
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 14 publications
5
125
2
Order By: Relevance
“…Since CBZ is known to inhibit voltage-sensitive Na + channels (Kuo et al, 1997;Rush and Elliott, 1997), the effect observed previously could be due to a reduction of the extent of depolarization. Thus, we analyzed the role of TTX-sensitive Na + channels on the increase of the [Ca 2 + ] i induced by kainate, and found that they are not involved in the depolarization caused by kainate, probably because they inactivate after the onset of depolarization.…”
Section: Effect Of Cbz On Kainate-mediated [Ca 2 + ] I Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since CBZ is known to inhibit voltage-sensitive Na + channels (Kuo et al, 1997;Rush and Elliott, 1997), the effect observed previously could be due to a reduction of the extent of depolarization. Thus, we analyzed the role of TTX-sensitive Na + channels on the increase of the [Ca 2 + ] i induced by kainate, and found that they are not involved in the depolarization caused by kainate, probably because they inactivate after the onset of depolarization.…”
Section: Effect Of Cbz On Kainate-mediated [Ca 2 + ] I Responsesmentioning
confidence: 99%
“…CBZ limits sustained high-frequency repetitive-firing of sodium-dependent action potentials of central neurons in cell culture at therapeutic concentrations (MacDonald and Kelly, 1993;Morimoto et al, 1997). This effect is commonly ascribed to a voltage-dependent inhibitory effect on voltage-gated Na + channels (Kapetanovic et al, 1995;Kuo et al, 1997;Rush and Elliott, 1997). However, the mechanisms underlying the effects of this AED have not been completely identified, and are still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbamazepine is thought to have a similar working mechanism. However, the affinity of carbamazepine for inactivated sodium channels is around 3 times lower than that of phenytoin [11]. Phenytoin, like all other antiepileptic drugs, has adverse effects, including gingival hyperplasia, skin disorders, cerebellar atrophy, ataxia, polyneuropathy, and impact on liver function.…”
mentioning
confidence: 99%
“…4 State-dependent block of NaChs is an important mechanism of action of many anticonvulsants, local anesthetics, and antiarrhythmics, [6][7][8][9][10][11][12][13] which generally exhibit greater affinity for the open or inactivated states of the channel than for the resting state ( Fig. 1) and, as such, are considered use-dependent blockers.…”
mentioning
confidence: 99%